1995
DOI: 10.1021/bp00035a006
|View full text |Cite
|
Sign up to set email alerts
|

Improved Homogenization of Recombinant Escherichia coli following Pretreatment with Guanidine Hydrochloride

Abstract: Pretreatment of recombinant Escherichia coli, expressing human growth hormone inclusion bodies, with guanidine hydrochloride and Triton X-100 prior to high-pressure homogenization has been investigated. Homogenates were analyzed for protein release, viscosity, and particle size. We were able to reduce the number of passes required for cell disruption and the number of downstream processing steps required for the recovery of protein from inclusion bodies by pretreating cells with guanidine HCl and Triton X-100.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…On a large scale, cell disruption is usually done with either a high pressure homogenizer or a bead mill (Engler, 1990;Kula and Schutte, 1987). Increasing the number of passes through a high pressure homogenizer causes greater protein release, but also results in smaller particle size distributions (Agerkvist and Enfors, 1990;Bailey et al, 1995;Middelberg et al, 1991;Titchener-Hooker et al, 1991). Smaller cell debris has a detrimental effect on subsequent downstream processing unit operations (Agerkvist and Enfors, 1990;Becker et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a large scale, cell disruption is usually done with either a high pressure homogenizer or a bead mill (Engler, 1990;Kula and Schutte, 1987). Increasing the number of passes through a high pressure homogenizer causes greater protein release, but also results in smaller particle size distributions (Agerkvist and Enfors, 1990;Bailey et al, 1995;Middelberg et al, 1991;Titchener-Hooker et al, 1991). Smaller cell debris has a detrimental effect on subsequent downstream processing unit operations (Agerkvist and Enfors, 1990;Becker et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In each of these models, the permeate flux decreases with decreasing particle size. As a result of this emphasis on larger particle sizes to improve downstream processing, some investigations have focused on reducing the extent of homogenization (Bailey et al, 1995;Harrison et al, 1991;Vogels and Kula, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…1), was to separate cell debris from the solubilized PMP. In the study by Bailey et al (1995) it was found that the addition of 4 M GdnHCl before homogenization of the E. coli cells gave smaller cell debris particles than with 1.5 M GdnHCl. The cell debris was not totally dissolved in 4 M GdnHCl, although the reaction was incubated for an extended period of time, but the membrane was affected in a way that it became more fragile.…”
Section: Solubilization Of Ibs and Separation Of Cell Debrismentioning
confidence: 98%
“…The cell debris was not totally dissolved in 4 M GdnHCl, although the reaction was incubated for an extended period of time, but the membrane was affected in a way that it became more fragile. In this study, 4 M GdnHCl or 1.5 M arginine was used at the solubilization step and, with support from the study by Bailey et al (1995) the cell debris was assumed to be particulate. Indeed, the endotoxin analysis results, seen in Table 4, indicate very clearly that most (97-99.5%) of the endotoxin was retained after the last separation step and when assuming that the endotoxin stays attached to the cell debris this implies that the cell debris was retained and that the separation was accomplished.…”
Section: Solubilization Of Ibs and Separation Of Cell Debrismentioning
confidence: 99%
“…The use of membranes, in place of batch centrifugation for IB collection and washing, resulted in three-fold increase in yield (Forman et al, 1990;Meagher et al, 1994), however, comparison with a more effective discstack centrifuge for cell debris and IB fractionation was not reported. A significant increase in the efficiency of cellular disruption following the addition of detergent and chaotrope has been reported (Bailey et al, 1995), but the addition of detergent complicates subsequent processing and does not eliminate the mechanical disruption step. The use of aqueous two-phase systems for direct recovery of IBs following mechanical disruption has been introduced (Braas et al, 2000), although IBs accumulated at the interface thus complicating their recovery and further processing.…”
Section: Advances In Ib Extraction and Solubilisation Technologymentioning
confidence: 99%